Development of leakage resistance monitoring scheme adapted to the changes of network isolation parametres - Харитонов, Александр Александрович; Ликаренко, Анатолий Григорьевич; Мельник, Ольга Евгеньевна; Ляхова, Надежда Николаевна (Eastern-European Journal of Enterprise Technologies, 2014)
Research materials show the effect of isolation capacitance on the conditions of leakage protection operation on alternating control current. The isolation monitoring method, based on using a differential current transformer was applied. To eliminate the destabilizing effect of changes in network isolation capacitance on the leakage relay operation conditions, conditions of adaptation of measuring element to this parameter were found. The research studies have allowed to develop functional diagram of leakage relay, in which functional failures such as the effect of unrecorded leakage currents from the rectified voltage poles on the measuring elements that are configured only to interact with the control current, formed by a special control current source; uncontrolled excess of value of leakage relay, allowable according to the performance charateristics by the actual network isolation capacitance, leading to functional failure because of the failure to provide standard for short-term leakage current through the human body were eliminated. The proposed scheme ensures performing protection functions such as continuous monitoring of the isolation resistance and current leakage values.